MANUFACTURING SINKING FISH FEED IN GAMPONG PADANG BAKJOK ACEH BARAT DAYA REGENCY: PEMBUATAN PAKAN IKAN TENGGELAM DI DESA PADANG BAK JOKKABUPATEN ACEH BARAT DAYA - Kurnia; Nurhatijah; Dedek Zulvira; Rachmat Hidayat; Humeira (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
The aim of Community Service (PKM) is to provide information to the public in introducing knowledge, one of which is the science of fisheries cultivation. Gampong Padang Bak Jok, Southwest Aceh Regency is a village that has the potential to produce drowned fish food. The method for implementing this activity is presenting the material to the people of Gampong Padang Bak Jok and continuing with making sinking fish food. All the people involved gain knowledge and understanding in making sinking fish food.  Village officials through Gampong-Owned Enterprises (BUMG) will facilitate the community in starting a business making sunken fish meal, both in terms of funding or providing tools and materials that will be needed by new cultivators.